Metode Activity Based Costing Dalam Penentuan Unit Cost Eksisi Fibroadenoma Mammae - Afiazka Luthfita; Susanto Susanto (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2016)
Indonesian began to operate health insurance program in 2014 with payment scheme by INA-CBG’s (Indonesian Case-Based Group). That makes hospital to have appropriate tariff calculation. Breast fibroadenoma (FAM)must have an appropriate tariff calculation because it will be increasing. One of a calculating method that can be used is Activity Based Costing (ABC) because this method can measure accurately cost out of any activity, improve the precision and accuracy in the details of charging fees. This study was descriptive quantitative. This study is limited to a patient with FAM cases that occurred in 2015 in patients using BPJS class III and without complications. The unit cost excision FAM at RS PKU Muhammadiyah Yogyakarta which is calculated by the method of activity-based costing is Rp 4,704,877. The difference with the hospital unit cost of Rp 218.923 hospitals are higher, while the difference with INA-CBG rates Rp Rp 679.471 smaller. The unit cost of service excision FAM still under INA-CBG’s rates, calculations by the ABC method is higer than the unit cost PKU Muhammadiyah Hospital. The management should be re-evaluated the tarif of this service.